Outcome and Complications of Phacoemulsification Combined with Pars Plana Vitrectomy - Shah, Irfan Ullah; Manzoor, Asif; Naeem, Muhammad; HussainAwan, Ayyaz; Zia Iqbal, Muhammad; Khan, Safeet Shahbaz; khan, Bilal (Journal of Neonatal Surgery, 2025)
Background: Phacoemulsification combined with pars plana vitrectomy is a widely used surgical technique for managing coexisting anterior and posterior segment pathologies. However, the procedure can lead to significant intraoperative and postoperative complications that impact clinical outcomes. Objective: To evaluate the outcomes and complications associated with phacoemulsification combined with pars plana vitrectomy. Material and Methods: This prospective observational study was conducted at the Department of Ophthalmology, Bakhtawar Amin College, Multan, over a period of six months from January 2024 to June 2024. A total of 196 patients underwent phacoemulsification combined with pars plana vitrectomy. The mean age of the patients was 47.93 years (SD ± 12.381). Intraocular pressure (IOP) was measured preoperatively, at 1 month, and at 12 months postoperatively. Intraoperative and postoperative complications were documented, and statistical analyses were performed to assess differences in IOP and complications. Results: The mean preoperative IOP was 14.65 mmHg (SD ± 3.693). Postoperatively, the mean IOP increased to 16.80 mmHg at 1 month and slightly decreased to 16.31 mmHg at 12 months, with statistically significant differences at both time points (p = 0.000 and p = 0.002, respectively). Most intraoperative complications were mild, with the lens capsule remaining intact in the majority of cases. Scleral sutures were frequently required, and postoperative complications included mild anterior segment reaction and fibrin presence. While complications were largely manageable, specific findings necessitate careful surgical technique and diligent postoperative care. Conclusion: Phacoemulsification combined with pars plana vitrectomy is a safe and effective procedure. However, the need for close monitoring of IOP and management of certain complications is essential to optimize outcomes